PENDIDIKAN ISLAM DALAM PERSPEKTIF SYED MUHAMMAD AL-NAQUIB AL-ATTAS - Rozi, Mohammad Fahrur (STAIN Pamekasan, 2010)
Abstract: The purpose of Islamic education is to create perfect wholly human beings (holistic). The concept of the perfect man in education starting from the values of adab (tadîb). Adab (tadîb) consists of talim (didoskeining) and tarbiyah (educating). Teaching and educationing as spiritual and material life entities of human beings is to improve the quality of virtue. Al-Attas is more likely use the concept of tadîb for Islamic education than talim or tarbiyah because the conceptual structure of tadîb already includes the elements of knowledge (ilm), teaching (talim) and good parenting (tarbiyah). Therefore, the concept tadîb is the most appropriate term showing the education in the broad sense.